Unlocking fast and highly reversible sodium storage in Fe-based mixed polyanion cathodes for low-cost and high-performance sodium-ion batteries. Issue 13 (9th March 2023) - Wang, Xu; Li, Huangxu; Zhang, Wei; Ge, Xiaochen; He, Liang; Zhang, Liuyun; Li, Shihao; Wen, Naifeng; Guo, Juanlang; Lai, Yanqing; Li, Simin; Zhang, Zhian
Abstract : The iron-based polyanionic material Na3 Fe2 (PO4 )P2 O7 is regarded as an excellent cathode due to its outstanding thermal stability and the three-dimensional (3D) open framework structure with facile sodium-ion transport. Abstract : The iron-based polyanionic material Na3 Fe2 (PO4 )P2 O7 is regarded as an excellent cathode due to its outstanding thermal stability and the three-dimensional (3D) open framework structure with facile sodium-ion transport. However, its inferior electronic conductivity and limited diffusion kinetics deteriorate its rate performance and cyclability. Herein, a rationally designed Ni doping strategy in Na3 Fe2 (PO4 )P2 O7 is developed to stabilize the crystal structure and to expand the migration path of Na + . The as-prepared cathode can exhibit a discharge capacity reaching 100.7 mA h g −1 at 0.1C and excellent cycling stability throughout 5000 cycles at 10C. Moreover, it maintains impressive high-temperature sodium storage behavior with negligible capacity degradation after 200 cycles at 1C and 60 °C. A highly reversible single-phase structural evolution is disclosed by in situ X-ray diffraction. Furthermore, the fast ionic/electronic diffusion kinetics is revealed through various electrochemical measurements and density functional theory calculations.